2017
DOI: 10.1016/j.jcin.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for the Use of Embolic Protection During Atherectomy for Femoral Popliteal Lesions

Abstract: Chronic total occlusion, in-stent restenosis, thrombotic, calcific lesions >40 mm, and atherosclerotic lesions >140 mm identified by peripheral angiography necessitate concomitant filter use during atherectomy to prevent embolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Other indications for filter are chronic total occlusion, in stent restenosis, thrombus, single-vessel runoff, and lesion length greater than 14cm. [7] This is consistent with our finding that longer treated length increases the risk of complication.…”
Section: Discussionsupporting
confidence: 93%
“…Other indications for filter are chronic total occlusion, in stent restenosis, thrombus, single-vessel runoff, and lesion length greater than 14cm. [7] This is consistent with our finding that longer treated length increases the risk of complication.…”
Section: Discussionsupporting
confidence: 93%
“…In the DEFINITIVE LE (Determination of EFfectiveness of the SilverHawk_ PerIpheral Plaque ExcisioN System (SIlverHawk Device) for the Treatment of Infrainguinal VEssels/Lower Extremities) registry, distal embolization occurred in 3.8% and arterial perforation occurred in 5.3% of cases . A recent single‐center study of femoral‐popliteal patients undergoing directional atherectomy with the routine use of distal embolic protection demonstrated presence of macroemboli in 62% of patients .…”
Section: Methodsmentioning
confidence: 99%
“…Both basket and balloon-based EPD showed high procedure and device success rates (>95%), with a limited number of complications. 10,12,24,21,25,35,36 In the last years, different studies and some trials confirmed a very low rate of DE, making the EPD very effective devices in preventing DE during lower limb interventions and dramatically reducing the risk of DE during mechanical atherectomy. 10,12,21,24 However, their use requires a certain technical experience as complications have been reported to occur during the procedure, such as dissection or spasm related to device motion, especially in diseased vessels or issues during retrieval.…”
Section: The Epdmentioning
confidence: 99%